Respuesta :

Answer:

option A

Step-by-step explanation:

   [tex]y - 9 = \frac{2}{3} (x + 7)\\\\ y - 9= \frac{2}{3} x + \frac{14}{3}\\\\ y = \frac{2}{3} x + \frac{14}{3} + 9\\\\y = \frac{2}{3}x + \frac{14 +27}{3}\\\\y = \frac{2}{3}x + \frac{41}{3}\\\\[/tex]

Therefore, slope of the given line is

                                                    [tex]m_ 1 = \ \frac{2}{3}[/tex]

Find the slope of the new line

The product of slope of  lines perpendicular to each other = - 1

That is ,

            [tex]m_ 1 \times m_2 = - 1\\\\\frac{2}{3} \times m_ 2 = - 1\\\\m_ 2 = - \frac{3}{2}[/tex]

Find the equation of the line.

[tex]Let \the \ given \ points \ be \ ( x_ 2 , y _ 2 ) = ( 2 , 3 ) \\\\(y- y_2) = m_2 (x - x_ 2)\\\\( y - 3 ) = - \frac{3}{2}(x - 2)\\\\y = -\frac{3}{2}x + \frac{3 \times 2}{2} + 3\\\\y = - \frac{3}{2} x +3+3\\\\y = - \frac{3}{2} x +6\\\\[/tex]

ACCESS MORE